2017
DOI: 10.1080/15389588.2017.1303682
|View full text |Cite
|
Sign up to set email alerts
|

Development of potential methods for testing congestion control algorithm implemented in vehicle-to-vehicle communications

Abstract: Objective: A channel congestion problem might occur when the traffic density increases because the number of basic safety messages carried on the communication channel also increases in vehicle-to-vehicle communications. A remedy algorithm proposed in SAE J2945/1 is designed to address the channel congestion issue by decreasing transmission frequency and radiated power. This study is to develop potential test procedures for evaluating or validating the congestion control algorithm. Methods: Simulations of a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Reference [8] proposed a control strategy based on a single-target Tabu Search algorithm in IoV (Internet of Vehicles). According to the minimized delay function, Tabu Search algorithm was applied to find the optimal value of transmission range and transmission rate.…”
Section: Related Researchmentioning
confidence: 99%
“…Reference [8] proposed a control strategy based on a single-target Tabu Search algorithm in IoV (Internet of Vehicles). According to the minimized delay function, Tabu Search algorithm was applied to find the optimal value of transmission range and transmission rate.…”
Section: Related Researchmentioning
confidence: 99%
“…There are only a few works in the context of the DSRC communication environment. Hsu et al [28] proposed a testing methodology for the algorithm in the DSRC environment. Rostami et al [29] showed that the algorithm indeed controls the CBR within the targeted range, and the IPG within the guideline set by the National Highway Traffic Safety Administration (NHTSA) [30] in most cases.…”
Section: A Standard J2945/1 Congestion Control Algorithmmentioning
confidence: 99%
“…The speeds of the vehicles are normally distributed, with the mean speed of 50 km/h and the deviation of 3 km/h. We use 300 bytes as the BSM size as recommended by Hsu et al [28]. The MCS index is 7, and the bandwidth is 10 MHz.…”
Section: Behavior Of J2945/1 Algorithm In C-v2xmentioning
confidence: 99%
“…The modulation and target coding rate are QPSK and 0.5, respectively. Although the message set dictionary SAE J2735 states that four 190-byte BSMs with digested and a single 300-byte BSM with the full security credential to be iterated [5], we will assume constant 300-byte packets as in many previous work [10], [14], [15], [27], to focus more on the impacts of the explicit reservation. As to the inefficiency that the varying message sizes may cause on the resource use, the readers are referred to Molina-Masegosa and Gozalvez [11].…”
Section: ) Packet Collision Between Vehicles Withmentioning
confidence: 99%
“…Finally, we omit the results for MCS 9, because it produces the identical qualitative results as MCS 7, only with lower packet delivery performances. We use 300 bytes as the BSM size as used in other works in the literature [10], [14], [15], [27]. Note that two different beacon sizes, such as prescribed by 3GPP TR 36.885 [4], more reselections may be necessary in case the resource allocation is only based on the smaller size, which could impact the performance [9].…”
mentioning
confidence: 99%